Implementation of the Greedy Algorithm in Phrase Pattern Matching for a Text Recognition System - Amelia, Risky; Sutabri, Tata (International Journal Scientific and Professional, 2025)
The Greedy pattern-matching algorithm is a phrase pattern-matching method that works by selecting the optimal solution at each step without backtracking. This approach is applied in text recognition systems for keyword search, natural language processing, and automatic text filters. This research analyzes the performance of the algorithm through computational experiments and literature review by evaluating the efficiency of execution time, number of character comparisons, and matching success rate. The results show that the algorithm offers high speed in pattern matching, especially on large datasets, as it is able to optimally shift the search index. However, its accuracy decreases when handling complex patterns or phrases that have many similarities. By combining this algorithm with heuristics or data preprocessing techniques, its drawbacks can be minimized, thus remaining an effective solution in text recognition systems that require fast and real-time processing.